Introduction to a lecture series on wind-wildlife interactions - Jill A. Shaffer; Todd E. Katzner (Пернатые хищники и их охрана)
The development of wind power as a renewable source of energy is rapidly growing globally and in Kazakhstan. However, wind facilities sometimes have negative environmental effects on wildlife. As wind energy expands in Kazakhstan, there is growing interest among a number of organizations and agencies to understand and mitigate the potential effects on biodiversity. This introductory lecture launches a series designed to review background information, concepts, and techniques that reflect the state of the art in the science, mitigation, and policy regarding windwildlife interactions within the USA. We will first discuss why it matters that we think about wildlife when we are developing wind energy by examining how wind facilities affect wildlife.